MENDORONG LITERASI KEUANGAN UMKM MELALUI PEMANFAATAN APLIKASI SIAPIK BERBASIS WEBSITE - Anugrah, Meilinda Dwi; Saputri, Ulfah Tika; Oktarini, Kurnia Widya; Febrianti, Devi; Firza, Edy (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2025)
Effective and efficient financial management is a crucial aspect in ensuring the sustainability of Micro, Small, and Medium Enterprises (MSMEs). One of the main challenges faced by MSME actors is the lack of understanding and skills in financial recording and reporting in accordance with accounting principles. This community service activity aims to improve the financial literacy and technical skills of the Wardrobe Rumaysha MSME in using the web-based SIAPIK application as a simple yet accurate financial recording tool. The method employed involves direct socialization and demonstration of the SIAPIK application, followed by hands-on assistance in its implementation. The results indicate that participants were able to understand the workflow of the application, input financial transactions independently, and generate simple digital financial reports. This initiative positively contributed to enhancing financial literacy among MSMEs, supporting transparency and accountability in business financial management..